“Comparativo de diferentes sistemas de tutoraje en el rendimiento de tomate (lycopersicon esculentum), en el bajo mayo” - Pezo Pinedo, Rita Maria (2000)
The work was made in the District of Moral, between the months of February and August of 1997, with the objective of to evaluate the effect of different tutoraje systems in the yield of the tomato variety Big River and to determine the relationship cost-benefit of the best treatments. The tutoraje systems that were used were: System of having hung (T1) as witness, System of a single stick (T2), espaldera System (T3) and English System or in V (T4). The used design was that of complete block at random, with four treatments and four repetitions. The total area of the work was of 629. 16 m2. The experimental evaluations were: Total percentage of prendimiento, Days to the floración, Number of flowers for inflorescence, Days to the maturation, Number of fruits for plant, plant Height to the transplant, plant Height at the end of the experiment, Number of plants harvested by experimental net area and Yield. In conclusion the treatment T4 (English System or in V) he/she obtained bigger yield with 25 160 Kg/ha. And the treatment T1 (System of having hung) he/she obtained smaller yield with 24 340 Kg/ha. Having a net value of the production for the treatment T4 (English System or in V) with 17 197.361 and for the treatment T1 (System of having hung) of 15 895. 56 and the relationship Cost-benefit was of 31.64 % and 34.69 %.